Biochemical investigations of Artocarpus spp. for cosmeceutical applications / Hazwani Mat Saad - Hazwani , Mat Saad (2022)
Cosmeceutical agents from natural origins which are presumably non-invasive, highly efficacious, and cost effective are exceptionally in demand by consumers nowadays. This study aimed to explore the potential of fifteen ethanolic extracts from the leaf, peel, and stem bark of five Malayan Artocarpus species, namely Artocarpus altilis (Parkinson) Fosberg, Artocarpus heterophyllus Lam., Artocarpus integer (Thunb.) Merr., Artocarpus elasticus Reinw. ex Blume, and Artocarpus rigidus Blume for their application in skin-lightening cosmeceutical by performing in vitro evaluations including anti-melanogenesis, radical scavenging, and ultraviolet (UV) protective activities. The study was then narrowed down to the bioassay-guided fractionation of the bioactive extract, followed by mechanistic analysis and encapsulation of the bioactive fraction. The A. heterophyllus stem bark and peel extracts showed potent anti-melanogenesis activity in reducing melanin content to 23–24% and inhibited the cellular tyrosinase activity with 1.85 and 1.42 folds stronger than kojic acid (positive control) at the concentration of 50 μg/mL. Whilst, the A. elasticus peel extract exhibited a remarkable radical scavenging activity on 2,2-diphenyl-1-picrylhydrazyl (DPPH•), 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS+•), and superoxide anion (O2−•). The A. heterophyllus stem bark extract which was identified as the bioactive extract in exerting anti-melanogenesis effect in B16F10 melanoma cells was selected for further analysis. A semi-purified fraction (H-3) from A. heterophyllus stem bark extract demonstrated the most pronounced anti-melanogenesis effect at 12.00 μg/mL by reducing melanin content to 22.86 ± 2.90% and inhibiting cellular tyrosinase activity at treatment concentration 33-folds lower than kojic acid, without being cytotoxic against B16F10 melanoma cells. Six chemical constituents in H-3 including two fatty acids and four iv flavonoids were identified via liquid chromatography-mass spectrometry (LCMS) analysis. Moreover, treatment with H-3 for 24 and 48 hours substantially scavenged intracellular reactive oxygen species (ROS) of hydrogen peroxide(H2O2)-challenged B16F10 melanoma cells by 1.8 and 4.4%, respectively. Based on the microarray profiling and real-time polymerase chain reaction (qPCR) analysis, H-3 downregulated Creb3l1, Creb3l2, Creb3l3, Mitf, Tyr, Tyrp1, and Dct genes in B16F10 melanoma cells, whereas the expression of Map3k20, Mapk14 (p38), and Foxo3 genes were markedly increased. Generally, these results demonstrated that H-3 exhibited its anti-melanogenesis activity in B16F10 melanoma cells through scavenging ROS and concurrent inhibition of the cyclic adenosine monophosphate (cAMP) and activation of the p38/mitogen-activated protein kinase (MAPK) signaling pathways. Due to the outstanding anti-melanogenesis effect of H-3, this bioactive fraction was encapsulated into the liposomes in order to enhance its cosmeceutical value. The incorporation of H-3 in liposomes yields vesicles with a particle size of 185 nm, a zeta potential of −38 mV, and encapsulation efficiency of 79%. The obtained results suggest that the encapsulation of H-3 in liposomes retained the anti-melanogenesis activity in B16F10 melanoma cells. Altogether, these findings indicate that H-3 from A. heterophyllus stem bark extract has the potential to be used as skin-lightening cosmeceutical agent in the treatment of skin hyperpigmentation.